PENINGKATAN KETERAMPILAN BERBICARA SISWA KELAS V SD NEGERI 8 WATAMPONE KABUPATEN BONE MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN - Muh. Idris Jafar; Sudarto, Sudarto; Fauziyah Amalia Masyura (Bajang Institute, 2025)
This study is a pre-experimental study that aims to determine whether the application of the Round Robin type cooperative learning model can or cannot improve the speaking skills of the fifth Grade students of SD Negeri 8 Watampone. The variables in this study are the Round Robin type cooperative learning model (independent variable) and the speaking skills (dependent variable). The population and the sample in this study were all of the fifth Grade students of SD Negeri 8 Watampone in totaling of 22 students. The data analysis technique used was a descriptive statistical technique. The results of this study indicate that the average pretest score was of 59.45 while the average posttest score was of 81.59. Conclusion: the implementation of the Round Robin type cooperative learning model can improve the speaking skills of the fifth Grade students of SD Negeri 8 Watampone, Bone Regency